ROLE OF SOE IN INCREASING PEOPLE'S WELFARE - Nachrawi, Gunawan (STIH Awang Long Samarinda, 2018)
This study aims to determine and understand the formulation of strategies for the management of state-owned enterprises in accordance with the law in order to enhance the role of SOEs as a supporter of economic development of Indonesia's economy for the welfare of society. Know and understand the contribution of SOEs in the framework of Indonesian economic development for the welfare of society. Knowing and understanding the legal politics of SOE management oriented to improve people's welfare. And know and understand the legal politics in the management of SOEs as a driver of economic development of Indonesia in the welfare state and social welfare. This research is included in the form of paradigm of normative juridical research that is research that emphasizes on the use of legal norms in writing. The result of this research is the contribution of SOEs in Economic Political Development in Indonesia by improving the management, especially the efficiency of the operation, will be able to face the market competition. Improvement measures include business restructuring, reducing the number of employees, implementing management control systems, and other strategic policies. BUMNs that do not perform management improvements will usually face various difficulties, especially in the financial sector.